Teachers’ Practice of Affective Strategies in Teaching Foreign Language Oral Tasks - Ouarda, KHOUNI (Sciences humaines, 2016)
تهدف الدراسة الى الاطلاع على ممارسة الاستاذ لاستراتيجيات التأثير في تدريس التطبيقات الكلامية للغة. انطلقنا من قناعة لكي يكون الاستاذ مؤثرا يجب ان يكون فعالا ويكون لديه بعض الخصائص والتي تم تصنيفها من طرف المتخصصين الي صفات شخصيه تسيير ألقسم تطبيق الدروس ومراقبة النجاح والتقدم. في هده ألدراسة تقم تقسيم الاستراتيجيات الي ثلاث مستوىات مستوى أللغة المتعلم ومحيط التعلم. لكي يكون الاستاذ مؤثرا ويحصل على نتائج جيدة  يجب ان تكون لديه صفات معينة في المستويات الثلاث. تمت الدراسة مع 15 استاذ لمادة التعبير الشفهي في ثلاث جامعات جزائرية باستعمال الملاحظة. اكدت النتائج بان المشاكل لا تتعلق بالصفات الشخصية للأستاذ بل الصفات المتعلقة بالتخطيط والأهداف مما يعكس فجوة في تعليم الاستاذ وتدريبه. لهدا الاصلاحات يجب ان تكون على مستوىين: مستوى تدريب الاستاذة ومستوى تحسين ظروف التعليم في الجامعة الجزائرية           The aim of this study is to explore teachers’ practice of affective strategies in teaching foreign language oral tasks. We started with the conviction that “to be affective, the teacher must be effective” and have certain qualities which are classified by most research in literature into four types: personal attributes, classroom management, implementing instruction and monitoring learners’ success. The participants are fifteen Oral expression teachers from three Algeria universities. The study is conducted through classroom observation. The Results reveal that problems are not related to the teacher as person but those qualities related to pedagogy; along recorded observation, there was a reflection of gap in teacher education and training which is represented in the lack of clear objectives, planning, variation, appropriate feedback and monitoring which are all essential for an effective teaching to take place. Therefore, recommendations should be made at two levels: teachers’ education and training and improving classroom conditions in the Algerian university.